2022
DOI: 10.1002/dc.25088
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma showing thymus‐like differentiation of the parotid gland: The brief report of cytomorphology and review of the literature

Abstract: Here, we report an extremely rare case of carcinoma with thymus‐like differentiation (CASTLE) of the parotid gland. CASTLE is a rare malignant epithelial tumor with thymic epithelial differentiation that arises in the thyroid gland or perithyroidal soft tissue. CASTLE of salivary gland origin is rare, with only nine published case reports to date (reported as “CASTLE” or “thymic carcinoma”). It is critical to diagnose salivary gland tumors using fine needle aspiration cytology. However, this tumor is rare, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, CASTLE has lower levels of keratinization or intercellular bridging. 14 It has been suggested that CD5 is a useful marker for identifying parotid CASTLE, though its use is limited because the characteristics of parotid CASTLE have not yet been fully elucidated. 11,12 Thyroidal CASTLE is thought to originate from the ectopic thymus, vestiges of thymopharyngeal duct, or branchial pouch remnants (including remnants of the postbranchial body formed from the fourth pharyngeal pouch or solid cell nest of the thyroid gland).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CASTLE has lower levels of keratinization or intercellular bridging. 14 It has been suggested that CD5 is a useful marker for identifying parotid CASTLE, though its use is limited because the characteristics of parotid CASTLE have not yet been fully elucidated. 11,12 Thyroidal CASTLE is thought to originate from the ectopic thymus, vestiges of thymopharyngeal duct, or branchial pouch remnants (including remnants of the postbranchial body formed from the fourth pharyngeal pouch or solid cell nest of the thyroid gland).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SCC, CASTLE is positive for p63 and CK5/6. However, CASTLE has lower levels of keratinization or intercellular bridging 14 . It has been suggested that CD5 is a useful marker for identifying parotid CASTLE, though its use is limited because the characteristics of parotid CASTLE have not yet been fully elucidated 11,12 …”
Section: Discussionmentioning
confidence: 99%